Angina and Non-Obstructive Coronary Artery (ANOCA) Patients with Coronary Vasomotor Disorders - Sarena La; Rosanna Tavella; Jing Wu; Sivabaskari Pasupathy; Christopher Zeitz; Matthew Worthley; Ajay Sinhal; Margaret Arstall; John A. Spertus; John F. Beltrame (Life, 2023)
Angina and Non-Obstructive Coronary Artery (ANOCA) patients often lack a clear explanation for their symptoms, and are frequently discharged with the label of “unspecified chest pain”, despite the availability of functional coronary angiography (provocative spasm and microvascular function testing) to identify potential underlying coronary vasomotor disorders. This study compared the outcomes of ANOCA patients with a coronary vasomotor disorder diagnosis post elective coronary angiography to patients discharged with unspecified chest pain. Using the CADOSA (Coronary Angiogram Database of South Australia) registry, consecutive symptomatic patients (n = 7555) from 2012 to 2018 underwent elective angiography; 30% had ANOCA (stenosis <50%). Of this cohort, 9% had documented coronary vasomotor disorders diagnosed, and 91% had unspecified chest pain. Patients with coronary vasomotor disorders were younger and had a similar female prevalence compared with those with unspecified chest pain. New prescriptions of calcium channel blockers and long-acting nitrates were more common for the coronary vasomotor cohort at discharge. In the 3 years following angiography, both groups had similar all-cause mortality rates. However, those with coronary vasomotor disorders had higher rates of emergency department visits for chest pain (39% vs. 15%, p < 0.001) and readmissions for chest pain (30% vs. 10%, p < 0.001) compared with those with unspecified chest pain. This real-world study emphasizes the importance of identifying high-risk ANOCA patients for personalized management to effectively address their symptoms.